Hubungan Keputusan Pendanaan dan Kebijakan Dividen Terhadap Nilai Perusahaan - adminejurnal; Sri Winarsih Ramadana (Jurnal Manajemen, Ekonomi, Keuangan dan Akuntansi, 2020)
Abstract? This study aimed to determine the effect of funding decisions and dividend policy on firm value in LQ45 companies listed on the Indonesia Stock Exchange. The research method used in this research is a quantitative approach, with the population used in this study companies included in the LQ45 period from February 2015 to August 2019 on the Indonesia Stock Exchange (IDX), which became a sample of 45 companies, which then obtained 121 research observations using an unbalanced panel, where the number of time units is different for each individual. The results showed that funding decisions affect firm value. That indicates proper funding can help companies finance their operational activities and increase company growth. Some examples of appropriate funding decisions are the use of own capital, bank loans, or issuing shares. Proper funding decisions can also help companies reduce the cost of capital and increase profitability. Dividend policy affects firm value. It shows that the company may also retain too much profit and not pay a large enough dividend, which can make investors disappointed and feel that the company does not add enough value. This can reduce the company's stock price and reduce the company's value. Keywords: Funding Decision, Dividend Policy, Firm Value